The Political Power in Clash of Clans Vis-à-vis the Philippine Concept of Political Power - JANN ANTHONY; JOY MELYN J PORQUIS (Jurnal Studi Pemerintahan, 2016)
The study was focused primarily on the concept of political power which wasviewed through the virtual and actual world using the strategy of simulation. Along with simulation, primary and secondary data were used. With the limited sources, data were gathered mainly on direct observation on the game COC. Secondary data were taken on the literature reviews pertaining to the field of study including books, articles and mostly from internet sources. The study found out the existing political power being rooted in COC. Though, the concepts found in the game and in the Philippine government gave different conceptualizations, the presence of political power in the game is pervasive. As political power was identified to be simulated in COC, it generated new avenue for video games being used as an educational tool rather than just purely for entertainment. It aimed to make video games, by the use of simulation, become a stable political space or trend not just in studying power structure or of a political system but also all other political concepts. As the new generations are so hooked up in video games, they can use it as a field for practicing and enhancing their leadership skills which is a positive form of escapism.